Biologics in dermatologic therapy - An update - Coondoo Arijit (Wolters Kluwer Medknow Publications, 2009)
Biologics are protein molecules which are used in various diseases to target the specific points in the immunopathogenesis of the diseases. The molecules are produced by recombinant DNA technology. The molecules bind to the specific targets without interfering wtih rest of the pathogenetic pathways. Therefore the so called ′immunosuppressives′ have, although, a broader broader spectrum of action on immune system, their side-effects are also equally more. The biologics, because of their spefic action on the immune system, have very little side effects. The biologics which have revolutionized the treatment of various dermatologic diseases have been discussed here.